Cognitive style, self-handicapping and entrepreneurial orientation of the employees of an agroindustry of Santa Catarina - Nascimento, Sabrina; Silveira, Amélia; Both, Vanderlei (Revista de Administração da UFSM, 2020)
Purpose – The study aimed to relate cognitive styles (CS), self-handicapping (SH) behaviors and entrepreneurial orientation (EO) present in an agroindustry of Santa Catarina. These aspects, within the same perspective, presents alternatives in the human capital management and as something new, in order to create and expand knowledge. Design/methodology/approach – The research was descriptive, quantitative, survey, and had statistical procedures. The respondents were 46 administrative employees of this agroindustry. Findings – The results indicate the predominance of employees with quasi-analytical (31%) and adaptive (28%) cognitive styles. Low SH indexes in the surveyed agroindustry were examined, demonstrating the engagement in the search for the results expected. The EO was moderate, evidencing a conservative stance of the company. No significant differences were observed in the relationship between the constructs of CS, SH and EO. However, the relationship between SH, EO and gender confirmed significant differences. Higher SH indices were observed among males, and a higher EO index in females. This difference disappears, statistically, in the other relationships. The conclusion is that reason prevails in the decision-making process, with a commitment focused on achieving the results, with a more conservative than entrepreneurial attitude. Practical implications – The study of the relationship of Cognitive Style, Self-Handicapping, and Entrepreneurial Orientation, within the understanding of Human Capital Management, constitutes a new perspective, making it possible to broaden the understanding of the theme in terms of administrative practice. Originality/value – Studying Cognitive Style, Self-Handicapping, and Entrepreneurial Orientation, in the context of Human Capital Management, in an agroindustry, presents itself as original and valuable research, contributing to the Administration Theory.